Population-Based Surveillance of HiB Invasive Infections in Children in British Columbia, Alberta and Ontario -- 1995 to 1997 - David Scheifele; Alison Bell; Taj Jadavji; Wendy Vaudry; John Waters; Monika Naus; Jill Sciberras (Canadian Journal of Infectious Diseases)
OBJECTIVE: To assess vaccine effectiveness through enhanced disease surveillance following the change in childhood immunization programs in 1995, when all provinces and territories chose to use polyribosyl ribitol phosphate-tetanus protein (PRP-T) Haemophilus influenzae type b (Hib) conjugate vaccine, generally in combination with diphtheria-pertussis-tetanus inactivated polio vaccine (DPT-IPV) (as PENTA vaccine) because the protective efficacy of this regimen had not been directly measured.